On Fourth-Order Stable Difference Scheme for Hyperbolic Multipoint NBVP. (3rd October 2017) - Yildirim, Ozgur; Uzun, Meltem
ABSTRACT: This paper presents a fourth order of accuracy unconditionally stable difference scheme for the approximate solution of multipoint nonlocal boundary value hyperbolic problem in a Hilbert space with a self-adjoint positive definite operator. Stability estimates for the solution of this difference scheme are established. To support the theoretical statements, some results of numerical experiments are presented using finite difference method.